Effect of Farming Systems on Soil Carbon Sequestration and Crop Yield of Paddy (Oryza sativa L.) in Irrigated Rice Field - Mujiyo Mujiyo; Suciati Dwi Nuraeni; Jauhari Syamsiyah; Aktavia Herawati (Environment and Natural Resources Journal, 2024)
Carbon sequestration is obtained from the total accumulation of the element in both soil and plants. The enhancement has the capacity to reduce greenhouse gas emissions and influence soil quality and fertility, thereby affecting plant biomass and crop yield. Therefore, this research aimed to compare the total carbon sequestration in rice field with different farming systems, determine soil characteristics, and identify the correlation between the total carbon sequestration and impact on rice yield. An exploratory-descriptive method was used through field survey and laboratory analysis. The locations were mapped by overlaying the Indonesian landform map of the Girimarto District with various rice field systems, soil types, and slopes. Furthermore, the 12 Land Mapping Units (LMU) with 3-time repetitions resulted in 36 sampling points. Data were processed by calculating total carbon sequestration and statistical tests such as one-way ANOVA and Pearson's correlation. The results showed that rice field farming systems affected the total carbon sequestration. Organic farming had the highest total carbon sequestration value of 72.49 Mg/ha and the increase had a strongly positive correlation with crop yield of paddy. Crop yield in organic farming were higher than in semi-organic and conventional systems by 8.92 tons/ha. Factors that determined total carbon sequestration were soil C-organic and microbial biomass C. The suggested improvement recommendations were the transition of conventional and semi-organic farming as well as adding a variety of organic fertilizers such as biofertilizers.